Este tren no está destinado a la gloria Un estudio de ferropaisajes literarios - Ravasio, Paola (Ensayos InterAmericanos, 2020)
The book "este tren no está destinado a la gloria" (this train is not destined for glory) revolves around the metaphor of literary ferro-landscapes. Conceived as narrative nodes created around the mobility of human and material capital by train, and at the same time interdependent of the economies that move such capital, this book approaches the literary representation of the railway world in narratives located in the Panama Canal Zone, through the Central American banana enclaves and follows the migrant caravan that crosses Mexico on La Bestia (The Beast). Ravasio reveals in her study a dialectic of in/mobilities where literary ferro-landscapes narratologically correlate spatial displacement with social immobility, exposing the exiles of modernity in their inglorious journey through the Americas.